Family sexual communication and sexual attitudes: understanding the influence on couples sexual communication - Mallory, Allen Burnell Sears (Kansas State University, 2016)
Quality of couples sexual communication remains an understudied area, despite its link with important relational outcomes such as relationship satisfaction, sexual satisfaction and condom use. Using a sample of 441 college students, this study examined how parent-child sexual communication (frequency, quality and permissive and restrictive messages) is related to sexual attitudes (permissive and idealistic) and couples sexual communication. Results suggests quality of couples sexual communication was positively related to frequency of parent-child sexual communication and negatively related to quality of parent-child sexual communication. There was not a significant relationship between the types of messages about sexuality from parents and quality of couples sexual communication. However, permissive parental messages were positively related to permissive sexual attitudes and restrictive parental messages was negatively related to permissive sexual attitudes. Idealistic sexual attitudes were found to be positively related to couples sexual communication. Finally, idealistic sexual attitudes marginally mediated the relationship between quality of parent-child sexual communication and quality of couples sexual communication. Clinical and research implications are discussed.
Keywords: Parent-child sexual communication; Couples sexual communication; Sexual attitudes